Copper alloy material for wind power sliding bearing and preparation method thereof
By adding Bi and graphite powder to wind-powered sliding bearings, and using laser-guided continuous casting technology to distribute graphite content gradients, combining Ni and Cr elements, the problems of insufficient self-lubricating capacity and graphite segregation of wind-powered sliding bearings are solved, achieving good results Lubricating performance and high temperature stability.
Patent Information
- Application Number
- CN202410920556.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-07-10
AI Technical Summary
The self-lubricating capacity of wind-powered sliding bearings is insufficient under low-speed heavy-load conditions, resulting in increased friction. The mechanical properties of existing copper alloy materials decrease and Bi are prone to fall off after adding Bi. The graphite powder sintering process has problems of reduced porosity and hardness.
0.5%-1% Bi and 0.15%-0.25% graphite powder were added to the copper alloy material, and the graphite content formed a gradient distribution from the inside of the Cu matrix to the surface through laser-guided continuous casting process, combining Ni and Cr elements to reduce graphite Separation, laser directional scanning is used to enhance interface bonding intensity.
It achieves good self-lubricating performance and high-temperature lubrication capabilities in wind-powered sliding bearings, avoids excessive segregation of graphite and Bi fall-off, ensures the material's load-bearing capacity and lubrication performance, and improves the interface bonding strength.
Smart Images

Figure CN118895440B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper alloy material for a wind power sliding bearing and a preparation method thereof, belonging to the technical field of surface treatment. Background Art
[0002] Sn bronze is a commonly used sliding bearing material. Its main advantage is its high load-bearing capacity and ability to meet heavy-load requirements. However, its biggest drawback is its insufficient self-lubricating ability, which makes it easy for the sliding bearing to bite during operation. The lack of self-lubricating ability of Sn bronze is particularly prominent under low-speed and heavy-load conditions. Wind power sliding bearings are typical low-speed and heavy-load conditions. It is difficult for sliding bearings to form a continuous and stable lubricating oil film under low-speed and heavy-load conditions, accompanied by a large amount of boundary friction, mixed friction, and even dry friction. In addition, it is particularly difficult for wind power sliding bearings to form oil film lubrication during the start-stop stage, and each wind power sliding bearing starts and stops more than 2,000 times per year on average. This requires that wind power sliding bearings have good self-lubricating properties during the start-stop stage, and have the ability to further enhance their own lubrication properties when abnormal friction occurs during operation. When the sliding bearing bites, the temperature rises sharply, which can be as high as several hundred degrees Celsius, and even thousands of degrees Celsius in some places. This requires the sliding bearing material to have good high-temperature lubrication ability.
[0003] As a solid lubricant, Bi is soft in texture and has a low melting point. When abnormal friction occurs in sliding bearings, the temperature always rises. At this time, Bi free in the Cu matrix begins to melt and precipitate to form a liquid lubricating film on the surface of the sliding bearing, which improves the self-lubricating ability of the sliding bearing, prevents the abnormal friction from further deteriorating, prevents seizure, and maintains the normal operation of the sliding bearing. However, the addition of Bi has a significant adverse effect on the mechanical properties of the copper alloy, thereby reducing the load-bearing capacity. On the other hand, due to the brittleness of Bi, Bi is easy to fall off. Excessive Bi content leads to the shedding of too many Bi particles, which in turn has an adverse effect on the lubrication performance of the sliding bearing material. Therefore, the Bi content needs to be strictly controlled so as not to affect the strength of the sliding bearing material and ensure sufficient load-bearing capacity.
[0004] As a solid lubricant, graphite material has excellent self-lubricating properties and high temperature resistance, and can provide stable and continuous lubrication capabilities at all operating temperature stages of sliding bearings. In addition, graphite and Cu matrix are completely immiscible. On the one hand, the current powder sintering process has the problem of porosity. On the other hand, only the graphite distributed near the surface can play a lubricating role. The graphite in the powder sintering material is distributed in various positions in the Cu matrix. Generally, the graphite content must be added to 6%-8%wt to have good self-lubricating properties. This proportion of graphite content has reduced the hardness of the copper alloy to below 60HB, and it no longer has the load-bearing capacity required for wind power sliding bearings. Therefore, sliding bearing materials that give full play to the excellent and stable solid lubrication properties of graphite and the high-temperature liquid lubrication properties of Bi have broad application prospects in the field of wind power sliding bearings. Therefore, a wind power sliding bearing copper alloy material and a preparation method thereof are urgently needed. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and provide a copper alloy material for wind power sliding bearings. The material has moderate hardness, meets good self-lubricating properties, and is particularly suitable for application to the surface of wind power sliding bearings.
[0006] At the same time, the present invention provides a method for preparing a copper alloy material for a wind power sliding bearing, wherein the graphite content forms a gradient distribution from the inside of the Cu matrix to the surface, thereby improving the surface self-lubricating performance.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A copper alloy material for wind power sliding bearings, comprising 99.75%-99.85%wt bronze powder and 0.15%-0.25%wt graphite powder, with a hardness between 100HB-110HB;
[0009] The composition of the bronze powder is: Sn: 10%-11%wt, Ni: 1%-2%wt, Bi: 0.5%-1%wt, Cr: 0.05%-0.1%wt, and the balance is Cu.
[0010] Preferably, the bronze powder has a particle size of 25 μm-85 μm, and the graphite powder has a particle size distribution of 2 μm-6 μm.
[0011] Preferably, the bronze powder further comprises P, B, and Ti, with a single or combined addition amount of 0.15 to 0.25%wt.
[0012] Preferably, the wind power sliding bearing comprises a wind power planetary shaft; the diameter of the wind power planetary shaft is 300-500 mm.
[0013] Preferably, the graphite content forms a gradient distribution from the inside of the matrix to the surface of the copper alloy material.
[0014] A method for preparing a copper alloy material for a wind power sliding bearing, characterized in that it comprises the following steps: after melting bronze powder and graphite powder uniformly mixed in proportion, obtaining an alloy liquid, directionally casting it on the surface of the wind power sliding bearing through a casting and drainage nozzle, and simultaneously using a laser with a power of 1200W to 1800W to directionally scan the interface between the molten copper alloy material and the wind power sliding bearing during casting, so as to guide the interface wetting and bonding, so as to enhance the interface bonding strength;
[0015] Laser directional scanning includes scanning at 90° perpendicular to the casting direction and scanning at 45° perpendicular to the casting direction;
[0016] The laser beam is only scanned perpendicular to the casting direction. In the casting direction, the laser head as a whole keeps moving in the same direction and at the same speed as the casting. When scanning at 90° perpendicular to the casting direction, the laser head is set at 90° perpendicular to the surface of the wind turbine sliding bearing. When scanning at 45° perpendicular to the casting direction, the laser head is set at an angle of 45° to the surface of the wind turbine sliding bearing.
[0017] First, a 90° directional scan is performed perpendicular to the casting direction. The scanning width is 1.5 to 1.7 times the width of the casting flow nozzle. The laser directional scanning frequency is 50 to 150 Hz, and the spot diameter is 2 to 3 mm. The casting flow nozzle and laser forward speed are 10 to 25 mm / s.
[0018] Then perform directional scanning at 45° perpendicular to the casting direction. The scanning width is 1.5 to 1.7 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50 to 150 Hz, and the spot diameter is 2 to 3 mm. The laser forward speed is 10 to 25 mm / s.
[0019] In the present invention, the laser scans in front between the 90° laser scanning and the casting, and the casting is carried out subsequently, while the 90° scanning is performed. After the casting, the surface is scanned once at 45°, so as to clean and remove carbon from the surface.
[0020] Preferably, the interface bonding strength is at least 210 MPa.
[0021] Preferably, before casting the alloy liquid, the casting interface and the substrate are preheated by laser.
[0022] Preferably, the casting and drainage nozzle has a width of 1.5 to 2.5 mm, a length of 5 to 8 mm, and a working distance between the casting and drainage nozzle and the highest point of the wind power sliding bearing of 1.2 to 2 mm; the casting and drainage nozzle is made of high temperature resistant ceramics.
[0023] The invention discloses an application of a copper alloy material for a wind power sliding bearing in a wind power sliding bearing.
[0024] The present invention has the following beneficial effects:
[0025] A copper alloy material for wind power sliding bearing material, wherein 0.5%-1%wt of Bi element and 0.15%-0.25%wt of graphite powder are added to the copper alloy to make the copper alloy material have good self-lubricating properties. Graphite has good self-lubricating properties below 600°C, and can provide stable lubrication for wind power sliding bearings from normal working state to abnormal friction high temperature state. At the same time, the addition of Bi can melt and precipitate to form liquid lubrication when the wind power sliding bearing is in the abnormal friction temperature rise stage, further enhancing the lubrication ability, timely eliminating abnormal friction, and preventing bite. The laser-guided continuous casting process is adopted to achieve a good lubrication effect when the graphite addition amount is 0.15%-0.25%wt. Graphite is insoluble in Cu matrix, and graphite will have specific gravity segregation in Cu matrix melt due to the difference in specific gravity. Adding Ni and Cr to the copper alloy can reduce the segregation of graphite in Cu matrix caused by density difference. Under high temperature conditions, C in graphite can partially enter the Ni lattice to form a solid solution combination, and can also form C compounds with Cr to form a compound combination. The two together form a "pinning" effect on graphite, alleviating the specific gravity segregation of graphite. Avoid excessive segregation of graphite on the surface of the Cu matrix and lose its application value. Furthermore, the laser-guided continuous casting uses a local casting method to make the solidification speed after casting extremely fast, further shortening the graphite segregation time. In turn, the serious segregation of graphite is avoided. The graphite content forms a gradient distribution from the inside of the Cu matrix to the surface (the graphite content gradient increases from the inside of the Cu matrix to the surface), which improves the surface self-lubricating performance. At the same time, the content of graphite in the Cu matrix is small, and the particle size is very small to avoid obvious splitting of the matrix, thereby ensuring that the strength of the Cu matrix is not significantly weakened. The graphite particle size of 2um-6um can form a uniform and continuous distribution, and can form a continuous lubricating film on the sliding surface when the sliding bearing is running. The continuous graphite lubricating film provides lubrication while also reducing the negative impact of Bi particle shedding on the friction and wear performance of the sliding bearing. As a result, graphite and Bi form a mutually coordinated and promoting role in lubrication. Experimental results show that bronze powder containing Ni: 1%-2%wt and Cr: 0.05%-0.1%wt can make the hardness of the copper alloy material reach 100HB-110HB while taking into account the improvement of the interface bonding between graphite and Cu matrix, and obtain an ideal graphite segregation distribution.
[0026] The laser guided continuous casting of the present invention preheats the casting interface and the substrate by laser before casting the alloy liquid. On the one hand, the oxide layer at the interface is broken to guide the wetting of the casting alloy liquid. On the other hand, the laser preheating of the substrate also promotes good bonding at the interface. The interface bonding strength reaches 210Mpa. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a metallographic diagram of the present invention;
[0028] Figure 2 It is the metallographic diagram of comparative example 1;
[0029] Figure 3 This is the metallographic diagram of Comparative Example 4. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0031] Example 1
[0032] A copper alloy material for wind power sliding bearings, comprising 99.7%wt bronze powder and 0.25%wt graphite powder, with a hardness of 100HB;
[0033] The composition of the bronze powder is: Sn: 10% wt, Ni: 1% wt, Bi: 0.5% wt, Cr: 0.05% wt, and the balance is Cu.
[0034] Preferably, the bronze powder has a particle size of about 25 μm, and the graphite powder has a particle size of about 2 μm.
[0035] Preferably, the wind power sliding bearing is a wind power planetary shaft; the diameter of the wind power planetary shaft is 500 mm.
[0036] Preferably, the graphite content forms a gradient distribution from the inside of the matrix to the surface of the copper alloy material.
[0037] A method for preparing a copper alloy material for a wind power sliding bearing comprises the following steps: after melting bronze powder and graphite powder uniformly mixed in proportion, obtaining an alloy liquid, directionally casting the alloy liquid on the surface of the wind power sliding bearing through a casting guide nozzle, and simultaneously using a 1200W laser to directionally scan the interface between the molten copper alloy material and the wind power sliding bearing during casting to guide the interface wetting and bonding, so as to enhance the interface bonding strength.
[0038] The casting drainage nozzle has a width of 1.5 mm and a length of 5 mm. The working distance between the casting drainage nozzle and the highest point of the wind power sliding bearing is 1.2 mm. The casting drainage nozzle is made of high temperature resistant ceramic.
[0039] Laser directional scanning includes scanning at 90° perpendicular to the casting direction and scanning at 45° perpendicular to the casting direction.
[0040] First, a directional scan is performed at 90° perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50 Hz, and the spot diameter is 2 mm. The casting drainage nozzle and laser forward speed are 10 mm / s.
[0041] Then, a directional scan is performed at 45° perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50 Hz, the spot diameter is 2 mm, and the laser forward speed is 10 mm / s.
[0042] The interface bonding strength reaches 210Mpa.
[0043] Preferably, before casting the alloy liquid, the casting interface and the substrate are preheated by laser.
[0044] The invention discloses an application of a copper alloy material for a wind power sliding bearing in a wind power sliding bearing.
[0045] like Figure 1 As shown, graphite is in a gradient distribution in the Cu matrix, gradually increasing near the upper layer, and Bi is evenly distributed in small particles.
[0046] Example 2
[0047] A copper alloy material for wind power sliding bearings, comprising 99.80%wt bronze powder and 0.20%wt graphite powder, with a hardness of 103HB;
[0048] The composition of the bronze powder is: Sn: 10.5% wt, Ni: 1.5% wt, Bi: 0.8% wt, Cr: 0.07% wt, and the balance is Cu.
[0049] Preferably, the bronze powder has a particle size of about 85 μm, and the graphite powder has a particle size of about 6 μm.
[0050] Preferably, the wind power sliding bearing is a wind power planetary shaft; the diameter of the wind power planetary shaft is 300 mm.
[0051] Preferably, the graphite content forms a gradient distribution from the inside of the matrix to the surface of the copper alloy material.
[0052] A method for preparing a copper alloy material for a wind power sliding bearing comprises the following steps: preparing the material by a laser-guided continuous casting process, melting bronze powder and graphite powder uniformly mixed in proportion to obtain alloy liquid, and directionally casting the alloy liquid on the surface of the wind power sliding bearing through a casting and drainage nozzle, and simultaneously using a 1500W laser to directionally scan the interface between the molten copper alloy material and the wind power sliding bearing during casting to guide the interface wetting and bonding to enhance the interface bonding strength.
[0053] The casting drainage nozzle has a width of 2.0 mm and a length of 6 mm. The working distance between the casting drainage nozzle and the highest point of the wind power sliding bearing is 1.5 mm. The casting drainage nozzle is made of high temperature resistant ceramic.
[0054] Laser directional scanning includes scanning at 90° perpendicular to the casting direction and scanning at 45° perpendicular to the casting direction.
[0055] First, a directional scan is performed at 90° perpendicular to the casting direction. The scanning width is 1.6 times the width of the casting drainage nozzle. The laser directional scanning frequency is 100 Hz, and the spot diameter is 2.5 mm. The casting drainage nozzle and laser forward speed are 15 mm / s.
[0056] Then a directional scan is performed at 45° perpendicular to the casting direction. The scanning width is 1.6 times the width of the casting drainage nozzle. The laser directional scanning frequency is 100 Hz, the spot diameter is 2.5 mm, and the laser forward speed is 15 mm / s.
[0057] The interface bonding strength reaches 212Mpa.
[0058] Preferably, before casting the alloy liquid, the casting interface and the substrate are preheated by laser.
[0059] The invention discloses an application of a copper alloy material for a wind power sliding bearing in a wind power sliding bearing.
[0060] Example 3
[0061] A copper alloy material for wind power sliding bearings, comprising 99.85%wt bronze powder and 0.15%wt graphite powder, with a hardness of 110HB;
[0062] The composition of the bronze powder is: Sn: 11% wt, Ni: 2% wt, Bi: 1% wt, Cr: 0.1% wt, P: 0.25% wt, and the balance is Cu.
[0063] Preferably, the bronze powder has a particle size of about 50 μm, and the graphite powder has a particle size of about 3 μm.
[0064] Preferably, the wind power sliding bearing is a wind power planetary shaft; the diameter of the wind power planetary shaft is 400 mm.
[0065] Preferably, the graphite content forms a gradient distribution from the inside of the matrix to the surface of the copper alloy material.
[0066] A method for preparing a copper alloy material for a wind power sliding bearing, characterized in that it comprises the following steps: preparing the material by a laser-guided continuous casting process, melting bronze powder and graphite powder uniformly mixed in proportion to obtain alloy liquid, and directionally casting the alloy liquid on the surface of the wind power sliding bearing through a casting and drainage nozzle, and simultaneously using a 1800W laser to directionally scan the interface between the molten copper alloy material and the wind power sliding bearing during casting to guide the interface wetting and bonding to enhance the interface bonding strength.
[0067] The casting drainage nozzle has a width of 2.5 mm and a length of 8 mm. The working distance between the casting drainage nozzle and the highest point of the wind power sliding bearing is 2 mm. The casting drainage nozzle is made of a high temperature resistant copper alloy.
[0068] Laser directional scanning includes scanning perpendicular to the casting direction and scanning in the same direction as the casting direction.
[0069] First, a laser directional scan is performed perpendicular to the casting direction. The scanning width is 1.7 times the width of the casting drainage nozzle. The laser directional scanning frequency is 150 Hz and the spot diameter is 3 mm. The casting drainage nozzle and laser forward speed are 25 mm / s.
[0070] Then, a laser directional scan is performed in the same direction as the casting forward direction. The scanning width is 1.7 times the width of the casting drainage nozzle. The laser directional scanning frequency is 150 Hz, and the spot diameter is 3 mm. The laser forward speed is 25 mm / s.
[0071] The interface bonding strength reaches 217Mpa.
[0072] Preferably, before casting the alloy liquid, the casting interface and the substrate are preheated by laser.
[0073] The invention discloses an application of a copper alloy material for a wind power sliding bearing in a wind power sliding bearing.
[0074] Example 4
[0075] A copper alloy material for wind power sliding bearings, comprising 99.78%wt bronze powder and 0.22%wt graphite powder, with a hardness of 107HB;
[0076] The composition of the bronze powder is: Sn: 10.4% wt, Ni: 1.7% wt, Bi: 0.6% wt, Cr: 0.09% wt, P: 0.05% wt, B: 0.05% wt, Ti: 0.05% wt, and the balance is Cu.
[0077] Preferably, the bronze powder has a particle size of about 30 μm, and the graphite powder has a particle size of about 4 μm.
[0078] Preferably, the wind power sliding bearing is a wind power planetary shaft; the diameter of the wind power planetary shaft is 450 mm.
[0079] Preferably, the graphite content forms a gradient distribution from the inside of the matrix to the surface of the copper alloy material.
[0080] A method for preparing a copper alloy material for a wind power sliding bearing, characterized in that it comprises the following steps: preparing the material by a laser-guided continuous casting process, melting bronze powder and graphite powder uniformly mixed in proportion to obtain alloy liquid, and directionally casting the alloy liquid on the surface of the wind power sliding bearing through a casting and drainage nozzle, and simultaneously using a 1600W laser to directionally scan the interface between the molten copper alloy material and the wind power sliding bearing during casting to guide the interface wetting and bonding to enhance the interface bonding strength.
[0081] The casting drainage nozzle has a width of 1.8 mm and a length of 6 mm. The working distance between the casting drainage nozzle and the highest point of the wind power sliding bearing is 1.7 mm. The casting drainage nozzle is made of high temperature resistant ceramic.
[0082] Laser directional scanning includes scanning at 90° perpendicular to the casting direction and scanning at 45° perpendicular to the casting direction.
[0083] First, a 90° directional scan was performed perpendicular to the casting direction. The scanning width was 1.5 times the width of the casting nozzle. The laser directional scanning frequency was 150Hz, and the spot diameter was 2.5mm. The casting nozzle and laser forward speed were 16mm / s.
[0084] Then a directional scan is performed at 45° perpendicular to the casting direction. The scanning width is 1.6 times the width of the casting drainage nozzle. The laser directional scanning frequency is 75 Hz, the spot diameter is 2 mm, and the laser forward speed is 20 mm / s.
[0085] The interface bonding strength reaches 215Mpa.
[0086] Preferably, before casting the alloy liquid, the casting interface and the substrate are preheated by laser.
[0087] The invention discloses an application of a copper alloy material for a wind power sliding bearing in a wind power sliding bearing.
[0088] Comparative Example 1
[0089] The only difference between this comparative example and Example 1 is that the copper alloy material used for the wind power sliding bearing material does not contain graphite powder.
[0090] like Figure 2As shown, adding Bi element to copper alloy will not produce grain boundary segregation and coarsening of Bi phase through laser-guided continuous casting process, Bi is evenly distributed in small spheres, and the size of Bi phase spheres is about 5μm, which is basically the same as the oil film thickness when the wind power sliding bearing is working. Therefore, the fine Bi phase precipitates and falls off during the tooling process of the sliding bearing to play a self-lubricating role without causing a decrease in wear resistance and friction reduction performance. At the same time, the micropores generated after the precipitation and shedding of the fine Bi phase can absorb and store lubricating oil through capillary action to form a stable oil film and improve the lubrication capacity of the bearing. However, since no graphite powder is added in this comparative example, its self-lubricating effect is not as good as that of Example 1, and its hardness is also reduced, and the load-bearing capacity required by the wind power sliding bearing is reduced.
[0091] Comparative Example 2
[0092] The only difference between this comparative example and comparative example 1 is that when the Bi content is higher than 1% (i.e., the Bi content is 1.2%), the hardness of the copper alloy further decreases. Too low hardness will reduce the bearing capacity and structural stability of the sliding bearing. In addition, the increase in Bi content will also cause the size of the Bi phase to increase, and the precipitation and shedding of the large-sized Bi phase will have an adverse effect on the wear of the wind power sliding bearing under heavy load conditions.
[0093] Comparative Example 3
[0094] The difference between this comparative example and comparative example 1 is that when the Bi content is lower than 0.5% (ie, the Bi content is 0.4%), the Bi phase in the copper alloy is too small to form a sufficient amount of precipitation and cannot effectively play the role of lubrication and wear reduction.
[0095] Comparative Example 4
[0096] The only difference between this comparative example and comparative example 1 is that the laser-guided continuous casting process is replaced by the conventional sintering process and casting process. Figure 3 As shown in the figure, the traditional sintering process and casting process have the problems of Bi phase segregation and coarseness. On the one hand, the segregation of Bi phase at the grain boundary leads to a significant reduction in the strength of the copper alloy material; on the other hand, the coarse Bi phase falls off from the steel matrix, resulting in a decrease in the wear resistance of the bearing material, and the deterioration of the friction reduction and anti-adhesion properties. In addition, the sintering process and casting process have the problems of high porosity of the alloy layer and low interface bonding strength, resulting in poor fatigue resistance of the material.
[0097] In the prior art, sliding bearings can be divided into two types: sliding bearing-shaft split type and sliding bearing-shaft integrated type. Split sliding bearings are usually called sleeves or bushes. Sleeves or bushes are made by sintering sliding bearing material powder with steel back by powder sintering process or casting sliding bearing material melt on steel back by casting process. The general process of sintering process: steel back surface cleaning - powder spreading - pre-sintering - rolling - sintering - rolling. The main disadvantages of sintering process are low interface bonding strength and high alloy porosity. Especially in the sintering of Bi-containing materials, porosity is a difficult problem to control well. For graphite-containing Cu-based sliding bearings, graphite powder and Cu alloy powder are evenly mixed and randomly distributed in the entire Cu matrix. A certain amount of graphite (usually more than 6%) must be added to effectively exert the lubricating effect of graphite. Too much graphite randomly and evenly distributed in the Cu matrix will cause obvious splitting of the Cu matrix and greatly reduce the strength of the Cu alloy.
[0098] The one-piece sliding bearing is a one-piece bearing material that is directly compounded on the shaft to make it a whole. The traditional casting process of this one-piece sliding bearing is difficult to achieve the outer surface casting of shaft workpieces. In addition, the traditional casting process requires the workpiece to be preheated as a whole, and the preheating temperature is usually 100-200℃ higher than the melting point of the sliding bearing material. High-temperature preheating will reduce the overall strength of the workpiece (strength is a very critical indicator for shaft workpieces). In addition, the overall preheating makes the alloy grains coarse due to the slow solidification rate of the alloy liquid. For elements such as Bi that are not soluble in Cu, they will be enriched and precipitated in large quantities at the grain boundaries, which directly leads to increased brittleness and insufficient strength of the Cu alloy. For additives with lower density such as graphite, serious specific gravity segregation will occur due to the untimely solidification of the Cu alloy, and the use value will be directly lost. Emerging additive manufacturing technologies are developing rapidly in the manufacturing of one-piece sliding bearings. For example, laser cladding, arc cladding and other similar directed energy deposition technologies. Laser cladding has the problem of high laser reflectivity and low laser energy utilization in Cu alloy processing, which leads to high probability of cracks and porosity in the clad Cu alloy layer. On the other hand, the hardness of laser clad Cu alloy layer is relatively high, generally higher than 140HB. Excessive hardness will significantly increase the risk of sliding bearing bite. Arc cladding has the problem of high porosity defect rate common in additive processes, and its application is limited because Bi-containing welding wire is difficult to produce. Directed energy deposition technology generally has the problem of generating a large number of pores in the material when directly processing and melting materials rich in C elements.
[0099] Comparative Example 5
[0100] The difference between this comparative example and comparative example 1 is that laser cladding is used to replace the laser-guided continuous casting process. When laser cladding is used to melt copper alloy powder, the efficiency of laser cladding copper alloy is not high due to the high reflection characteristics of copper alloy powder to laser, and due to the low thermal efficiency, there are many pores inside the copper alloy. This limits the application of laser cladding technology.
[0101] In addition, if graphite powder is added in this comparative example, the graphite is not suitable for direct melting by laser or arc, and the direct effect of laser and arc on graphite will cause a large number of pores.
[0102] Comparative Example 6
[0103] The only difference between this comparative example and comparative example 1 is that arc deposition is used to replace the laser-guided continuous casting process. Although arc deposition technology is more suitable for melting copper alloys, since the Bi element greatly reduces the strength and plasticity of the copper alloy, it is difficult to produce Bi-containing copper alloy welding wire, thereby limiting the application of arc deposition technology.
[0104] In addition, if graphite powder is added in this comparative example, the graphite is not suitable for direct melting by laser or arc, and the direct effect of laser and arc on graphite will cause a large number of pores.
[0105] Comparative Example 7
[0106] The difference between this comparative example and Example 1 is only that:
[0107] The laser is directional scanned at 90° perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50Hz and the spot diameter is 2mm. The casting drainage nozzle and laser forward speed are 10mm / s, and then another directional scan at 90° perpendicular to the casting direction is performed.
[0108] Comparative Example 8
[0109] The difference between this comparative example and Example 1 is only that:
[0110] The laser is directional scanned at 45° perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50Hz and the spot diameter is 2mm. The casting drainage nozzle and laser forward speed are 10mm / s, and then another directional scan at 45° perpendicular to the casting direction is performed.
[0111] Comparative Example 9
[0112] The difference between this comparative example and Example 1 is only that:
[0113] Laser directional scanning includes scanning at 90° perpendicular to the casting direction and scanning at 30° perpendicular to the casting direction;
[0114] First, a 90° directional scan is performed perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting flow nozzle. The laser directional scanning frequency is 50Hz, and the spot diameter is 2mm. The casting flow nozzle and laser forward speed are 10mm / s.
[0115] Then a directional scan is performed at 30° perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50 Hz, the spot diameter is 2 mm, and the laser forward speed is 10 mm / s.
[0116] Comparative Example 10
[0117] The difference between this comparative example and Example 1 is only that:
[0118] Laser directional scanning includes scanning at 90° perpendicular to the casting direction and scanning at 60° perpendicular to the casting direction;
[0119] First, a 90° directional scan is performed perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting flow nozzle. The laser directional scanning frequency is 50Hz, and the spot diameter is 2mm. The casting flow nozzle and laser forward speed are 10mm / s.
[0120] Then a directional scan is performed at 60° perpendicular to the casting direction. The scanning width is 1.5 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50 Hz, the spot diameter is 2 mm, and the laser forward speed is 10 mm / s.
[0121] The performance data of the embodiments and comparative examples are shown in Table 1 below.
[0122] Table 1 Performance data table
[0123]
[0124]
[0125] The hardness tested in this embodiment is the Brinell hardness, and the Brinell hardness test standard or method is universal. The friction coefficient is the most direct reflection of the self-lubricating performance. The friction coefficient test standard or method is universal.
[0126] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0127] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A copper alloy material for wind power sliding bearings, characterized in that: It includes 99.75%-99.85%wt bronze powder and 0.15%-0.25%wt graphite powder, and its hardness is between 100HB-110HB; The composition of bronze powder is: Sn: 10%-11% wt, Ni: 1%-2% wt, Bi: 0.5%-1% wt, Cr: 0.05%-0.1% wt, and the balance is Cu; The particle size of bronze powder is 25μm-85μm, and the particle size distribution of graphite powder is 2μm-6μm; The graphite content forms a gradient distribution from the inside of the copper alloy material matrix to the surface; The graphite content gradient increases from the inside to the surface of the Cu matrix; The interface bonding strength is at least 210Mpa; It is prepared by laser guided continuous casting process.
2. The copper alloy material for wind power sliding bearing according to claim 1, characterized in that: Bronze powder also includes P, B, Ti, with single or combined addition amounts of 0.15~0.25%wt.
3. The copper alloy material for wind power sliding bearing according to claim 1, characterized in that: The wind power sliding bearing includes a wind power planetary shaft; the diameter of the wind power planetary shaft is 300-500mm.
4. A method for preparing a copper alloy material for a wind power sliding bearing according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: melting bronze powder and graphite powder uniformly mixed in proportion to obtain alloy liquid, directionally casting the alloy liquid on the surface of the wind power sliding bearing through a casting guide nozzle, and simultaneously using a 1200W-1800W laser to directionally scan the interface between the molten copper alloy material and the wind power sliding bearing during casting to guide the interface wetting and bonding to enhance the interface bonding strength; Laser directional scanning includes scanning at 90° perpendicular to the casting direction and scanning at 45° perpendicular to the casting direction; First, perform directional scanning at 90° perpendicular to the casting direction. The scanning width is 1.5~1.7 times the width of the casting flow nozzle. The laser directional scanning frequency is 50~150Hz, and the spot diameter is 2~3mm. The casting flow nozzle and laser forward speed are 10~25mm / s. Then perform a directional scan at 45° perpendicular to the casting direction. The scanning width is 1.5~1.7 times the width of the casting drainage nozzle. The laser directional scanning frequency is 50~150Hz, and the spot diameter is 2~3mm; the laser forward speed is 10~25mm / s.
5. The preparation method according to claim 4, characterized in that: The interface bonding strength is at least 210Mpa.
6. The preparation method according to claim 4, characterized in that: Before casting the alloy liquid, the casting interface and the substrate are preheated by laser.
7. The preparation method according to claim 4, characterized in that: The width of the casting drainage nozzle is 1.5~2.5mm, the length is 5mm~8mm, and the working distance between the casting drainage nozzle and the highest point of the wind power sliding bearing is 1.2mm~2mm; the material of the casting drainage nozzle is high temperature resistant ceramic.
8. Use of the copper alloy material for wind power sliding bearings according to any one of claims 1 to 3 in wind power sliding bearings.
Citation Information
Patent Citations
Integral gradient self-lubricating bearing, and fabricating method
CN101092991A
Lead-free steel backing copper-based self-lubricating bearing
CN102678755A